The Impact of Lipid Corona on Rifampicin Intramacrophagic Transport Using Inhaled Solid Lipid Nanoparticles Surface-Decorated with a Mannosylated Surfactant - Eleonora Maretti; Cecilia Rustichelli; Magdalena Lassinantti Gualtieri; Luca Costantino; Cristina Siligardi; Paola Miselli; Francesca Buttini; Monica Montecchi; Eliana Leo; Eleonora Truzzi; Valentina Iannuccelli (MDPI AG, 2019)
The mimicking of physiological conditions is crucial for the success of accurate in vitro studies. For inhaled nanoparticles, which are designed for being deposited on alveolar epithelium and taken up by macrophages, it is relevant to investigate the interactions with pulmonary surfactant lining alveoli. As a matter of fact, the formation of a lipid corona layer around the nanoparticles could modulate the cell internalization and the fate of the transported drugs. Based on this concept, the present research focused on the interactions between pulmonary surfactant and Solid Lipid Nanoparticle assemblies (SLNas), loaded with rifampicin, an anti-tuberculosis drug. SLNas were functionalized with a synthesized mannosylated surfactant, both alone and in a blend with sodium taurocholate, to achieve an active targeting to mannose receptors present on alveolar macrophages (AM). Physico-chemical properties of the mannosylated SLNas satisfied the requirements relative to suitable respirability, drug payload, and AM active targeting. Our studies have shown that a lipid corona is formed around SLNas in the presence of Curosurf, a commercial substitute of the natural pulmonary surfactant. The lipid corona promoted an additional resistance to the drug diffusion for SLNas functionalized with the mannosylated surfactant and this improved drug retention within SLNas before AM phagocytosis takes place. Moreover, lipid corona formation did not modify the role of nanoparticle mannosylation towards the specific receptors on MH-S cell membrane.